Respuesta :
Answer:
=−71/3
Step-by-step explanation:3
+
1
−
6
=
7
2
{\color{#c92786}{3x}}+1{\color{#c92786}{-6x}}=72
3x+1−6x=72
−
3
+
1
=
7
2
{\color{#c92786}{-3x}}+1=72
−3x+1=72
2
Subtract
1
1
1
from both sides of the equation
−
3
+
1
=
7
2
-3x+1=72
−3x+1=72
−
3
+
1
−
1
=
7
2
−
1
-3x+1{\color{#c92786}{-1}}=72{\color{#c92786}{-1}}
−3x+1−1=72−1
3
Simplify
Subtract the numbers
Subtract the numbers
−
3
=
7
1
-3x=71
−3x=71
4
Divide both sides of the equation by the same term
−
3
=
7
1
-3x=71
−3x=71
−
3
−
3
=
7
1
−
3
−3−3x=−371
5
Simplify
Cancel terms that are in both the numerator and denominator
Divide the numbers
=−71/3
x=-\frac{71}{3}
x=−371